Partitioning of respired CO2 in newly sprouted Moso bamboo culms - Ye, Chongyu; Zeng, Qiangfa; Hu, Keda; Fang, Dongming; Hölscher, Dirk; Du, Huaqiang; Shi, Yongjun; Zhou, Yufeng; Berninger, Frank; Mei, Tingting; Zhou, Guomo (Frontiers in Plant Science, 2023)
Stem respiration (Rs) plays a vital role in ecosystem carbon cycling. However, the measured efflux on the stem surface (Es) is not always in situ Rs but only part of it. A previously proposed mass balance framework (MBF) attempted to explore the multiple partitioning pathways of Rs, including sap-flow-transported and internal storage of Rs, in addition to Es. This study proposed stem photosynthesis as an additional partitioning pathway to the MBF. Correspondingly, a double-chamber apparatus was designed and applied on newly sprouted Moso bamboo (Phyllostachys edulis) in leafless and leaved stages. Rs of newly sprouted bamboo were twice as high in the leafless stage (7.41±2.66 μmol m-2 s-1) than in the leaved stage (3.47 ± 2.43 μmol m-2 s-1). Es accounted for ~80% of Rs, while sap flow may take away ~2% of Rs in both leafless and leaved stages. Culm photosynthesis accounted for ~9% and 13% of Rs, respectively. Carbon sequestration from culm photosynthesis accounted for approximately 2% of the aboveground bamboo biomass in the leafless stage. High culm photosynthesis but low sap flow during the leafless stage and vice versa during the leaved stage make bamboo an good choice for exploring the MBF.